Manufacturing method of superabsorbent resin

By incorporating a redox pair into the monomer composition for superabsorbent resins, the method minimizes air bubble loss during radical polymerization, achieving improved porosity and water absorption rates in the final resin product.

JP7648290B2Active Publication Date: 2025-03-18LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023543453
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-11
Filing Date
2022-10-12
Publication Date
2025-03-18
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

Conventional radical polymerization methods using photoinitiators result in significant losses of carbon dioxide gas during foaming polymerization, leading to inadequate porosity and reduced water absorption rates in superabsorbent resins.

Method used

A method involving the use of a monomer composition that includes an acrylic acid monomer, an internal crosslinker, a photoinitiator, a heat initiator, a blowing agent, and a redox pair of reducing and oxidizing agents, which minimizes air bubble loss during foaming polymerization by initiating polymerization before significant carbon dioxide loss occurs.

Benefits of technology

This approach allows for the production of superabsorbent resins with a high degree of foaming, resulting in a significantly improved water absorption rate and enhanced surface area, suitable for various applications requiring high water absorption properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648290000001
    Figure 0007648290000001
Patent Text Reader

Abstract

The present invention relates to a method for producing a superabsorbent polymer that can minimize the loss of bubbles during foaming polymerization using a radical polymerization method. According to the method for producing a superabsorbent polymer of the present invention, a large number of small and uniform pores are formed, resulting in a high surface area. The superabsorbent polymer exhibits an excellent water absorption rate, and can be used in a variety of products that require high absorbency.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Cross-reference to related applications] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0187268 filed on December 24, 2021, and Korean Patent Application No. 10-2022-0129533 filed on October 11, 2022, and all contents disclosed in the documents of the Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for producing a highly water-absorbent resin. [Background technology]

[0003] Super absorbent polymers (SAPs) are synthetic polymeric substances capable of absorbing 500 to 1,000 times their own weight in water. They first came into practical use as sanitary products, and are now widely used in a variety of applications, including sanitary products such as baby diapers, as soil water retention agents in gardening, waterproofing materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution industry, and as materials for compresses.

[0004] In order to improve the water absorption rate of superabsorbent resin, a method of forming a porous structure by adding a blowing agent during polymerization is known. Carbon dioxide gas generated when the acrylic acid monomer, the main raw material of superabsorbent resin, meets with the blowing agent forms a large number of pores on the surface of the produced superabsorbent resin, thereby increasing the surface area of ​​the superabsorbent resin and improving the water absorption rate.

[0005] However, in the case of a conventional radical polymerization method using a photoinitiator, a large amount of carbon dioxide gas is lost before the polymerization progresses and the liquid monomer composition is converted into a solid state, so that the desired level of porosity cannot be achieved.

[0006] Therefore, in a method for producing a superabsorbent resin using a foaming agent, a method capable of compensating for the above-mentioned limit in radical polymerization is required. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide a method for producing a highly water-absorbent resin that can minimize bubble loss during foaming polymerization using a radical polymerization method. [Means for solving the problem]

[0008] In order to achieve the above object, the present invention provides preparing a monomer composition by mixing an acrylic acid monomer having an acidic group, at least a portion of which is neutralized; an internal crosslinking agent; a photoinitiator; a thermal initiator; a foaming agent; and a reducing agent and an oxidizing agent which form a redox pair with each other; preparing a hydrogel polymer by cross-linking the monomer composition; drying and grinding the hydrogel polymer to form a base resin in powder form; and A method for producing a superabsorbent resin, comprising the step of additionally crosslinking a surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer, The present invention provides a method for producing a superabsorbent resin, wherein the reducing agent and the oxidizing agent are each contained in an amount of more than 1 mol and not more than 13 mol per mol of the photoinitiator. Effect of the Invention

[0009] According to the manufacturing method of the present invention, it is possible to minimize the loss of bubbles during foaming polymerization by radical polymerization, and therefore to obtain a superabsorbent resin having a large number of small and uniform pores. The superabsorbent resin has a large surface area, and therefore exhibits a significantly improved water absorption speed, and can be used in various products that require high water absorption and have excellent absorbency such as water retention capacity and pressure absorption capacity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates a different meaning. In this specification, the terms "include", "comprise", "have" or "have" are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood as not precluding the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0011] Since the present invention can be modified in various ways and can have various forms, specific embodiments are described in detail below. However, this is not intended to limit the present invention to the specific disclosed form, and it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.

[0012] In the present specification, the term "base resin" or "base resin powder" refers to a polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer, which is dried and pulverized into a particle or powder form, and which is not surface-modified or surface-crosslinked.

[0013] The method for producing the highly water-absorbent resin of the present invention will be described in more detail below.

[0014] In the industrial production process of superabsorbent resin, the polymerization of the main raw material, acrylic acid monomer, is usually carried out by radical polymerization using a photoinitiator in a reactor equipped with a conveyor belt. This polymerization method has the advantage of being capable of continuous polymerization, but has the problem that during foaming polymerization using a foaming agent, a large amount of carbon dioxide gas generated when the foaming agent meets the monomer before the monomer composition is polymerized and becomes solid is lost into the atmosphere. If the carbon dioxide gas bubbles are lost in this way, the foaming degree of the superabsorbent resin becomes lower compared to the amount of foaming agent added, and as a result, the effect of improving the water absorption speed is not sufficiently obtained.

[0015] Therefore, the present inventors have studied a method for preventing the loss of bubbles even during continuous radical polymerization using a conveyor belt. As a result, the present inventors have confirmed that when a reducing agent and an oxidizing agent, which form an oxidation and reduction pair with each other, i.e., a redox pair, are added to the monomer composition and the content is more than 1 mole and less than 13 moles per mole of the photoinitiator contained in the monomer composition, the loss of bubbles generated from the foaming agent can be minimized and a large amount of smaller bubbles can be generated to produce a superabsorbent resin with a high degree of foaming, and thus completed the present invention.

[0016] Therefore, the method for producing a superabsorbent resin according to one embodiment of the present invention is as follows: preparing a monomer composition by mixing an acrylic acid monomer having an acidic group, at least a portion of which is neutralized; an internal crosslinking agent; a photoinitiator; a thermal initiator; a foaming agent; and a reducing agent and an oxidizing agent which form a redox pair with each other; preparing a hydrogel polymer by cross-linking the monomer composition; drying and grinding the hydrogel polymer to form a base resin in powder form; and The method includes a step of forming a surface cross-linked layer by additionally cross-linking the surface of the base resin in the presence of a surface cross-linking agent, wherein the reducing agent and the oxidizing agent are each contained in an amount of more than 1 mol and not more than 13 mol per mol of the photoinitiator.

[0017] The acrylic acid monomer is a compound represented by the following formula 1:

[0018] [Chemical formula 1] R 1 -COOM 1

[0019] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0020] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0021] Here, the acrylic acid monomer may have an acid group, and at least a part of the acid group may be neutralized. Preferably, the monomer is partially neutralized with an alkaline material such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. At this time, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree may be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer is precipitated, making it difficult to carry out smooth polymerization, and conversely, if the neutralization degree is too low, the absorbency of the polymer is greatly reduced and the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.

[0022] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition including the raw material of the superabsorbent polymer and the solvent, and may be an appropriate concentration in consideration of the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent polymer may be low, which may cause problems in terms of economy, whereas if the concentration is too high, a part of the monomer may be precipitated, or the efficiency of pulverization of the polymerized hydrogel polymer may be reduced, which may cause problems in the process, and the physical properties of the superabsorbent polymer may be deteriorated.

[0023] In the method for producing a superabsorbent resin of the present invention, the photoinitiator (photopolymerization initiator) used during polymerization is not particularly limited as long as it is one that is generally used in the production of superabsorbent resins.

[0024] On the other hand, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet rays, etc., and a certain amount of heat is generated as the polymerization reaction, which is an exothermic reaction, progresses. Therefore, in the present invention, a thermal initiator (thermal polymerization initiator) is used together with a photoinitiator.

[0025] The photoinitiator can be any compound capable of forming radicals by exposure to light such as ultraviolet light, without any limitations on its composition.

[0026] The photoinitiator may be, for example, one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, as a specific example of the acylphosphine, commercially available Lucirin TPO (Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide) or Irgacure 819 (Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) may be used. A wide variety of photoinitiators are well documented in Reinhold Schwalm's book "UV Coatings: Basics, Recent Developments and New Applications" (Elsevier, 2007), p. 115, and are not limited to the examples mentioned above.

[0027] The photoinitiator may be included in an amount of 0.001 parts by weight or more, 0.005 parts by weight or more, or 0.007 parts by weight or more, and 0.1 parts by weight or less, 0.05 parts by weight or less, or 0.01 parts by weight or less, based on 100 parts by weight of the acrylic acid monomer. If the content of the photoinitiator is too low, the polymerization rate is slow, and if the content of the photoinitiator is too high, the molecular weight of the superabsorbent resin is small, resulting in non-uniform physical properties.

[0028] The thermal initiator may be at least one selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8), and examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride. dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. A wide variety of thermal initiators are described in detail in Odian's book "Principle of Polymerization (Wiley, 1981)", p. 203, and are not limited to the above examples.

[0029] The thermal initiator may be included in an amount of 0.1 parts by weight or more, 0.15 parts by weight or more, or 0.2 parts by weight or more, and 1 part by weight or less, 0.8 parts by weight or less, 0.6 parts by weight or less, or 0.4 parts by weight or less, based on 100 parts by weight of the acrylic acid monomer. If the content of the thermal initiator is less than 0.1 parts by weight based on 100 parts by weight of the acrylic acid monomer, the amount of monomer remaining unreacted may increase, and if it exceeds 1 part by weight, discoloration of the resin may occur.

[0030] The monomer composition according to the embodiment of the present invention includes an internal crosslinking agent, which serves to crosslink the inside of a polymer formed by polymerizing an acrylic acid monomer, and is different from a surface crosslinking agent, which serves to crosslink the surface of the polymer.

[0031] As the internal crosslinking agent, for example, one or more selected from the group consisting of N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, (meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerin, and ethylene carbonate can be used.

[0032] The internal crosslinking agent may be contained in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.5 parts by weight or more, and 2 parts by weight or less, 1.5 parts by weight or less, or 1 part by weight or less, based on 100 parts by weight of acrylic acid.

[0033] As the foaming agent, organic and / or inorganic foaming agents generally used in the manufacture of superabsorbent resins can be used without limitation, for example, carbonate foaming agents, capsule-type foaming agents, etc. Among these foaming agents, carbonate foaming agents are preferably used because they are relatively inexpensive and easily generate carbon dioxide gas under acidic conditions.

[0034] The carbonate-based foaming agent may be, for example, one or more selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium bicarbonate, magnesium bicarbonate, and magnesium carbonate, but is not limited thereto.

[0035] The foaming agent can be used in an amount of 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less, based on 100 parts by weight of the acrylic acid monomer. If the amount of the foaming agent is too small, the bubbles generated during polymerization are insufficient, and the superabsorbent resin produced does not have sufficient porosity. If the amount of the foaming agent is too large, the porosity of the superabsorbent resin becomes too high, resulting in a problem of reduced mechanical strength.

[0036] The reducing agent and the oxidizing agent may be organic and / or inorganic compounds known to form a redox couple with each other. As an example, the reducing agent may be sodium metabisulfite and the oxidizing agent may be sodium persulfate, potassium persulfate, or ammonium persulfate. Or the reducing agent may be ascorbic acid and the oxidizing agent may be hydrogen peroxide.

[0037] An example may include sodium metabisulfite and sodium persulfate; or ascorbic acid and hydrogen peroxide as a redox couple.

[0038] The reducing agent and the oxidizing agent, i.e., the redox pair, undergo an oxidation-reduction reaction with each other in the monomer composition, and polymerization begins before photopolymerization begins due to radicals generated by the oxidation-reduction reaction of the redox pair. Therefore, when the monomer composition contains a redox pair, the photopolymerization rate is faster than when the redox pair is not present, and polymerization can be performed before significant carbon dioxide loss occurs, thereby minimizing bubble loss.

[0039] To ensure the above effect, the reducing agent and the oxidizing agent are each contained in an amount of more than 1 mole and not more than 13 moles per mole of the photoinitiator, and preferably in an amount of 1.3 moles or more, or 2 moles or more, and not more than 12 moles, not more than 10 moles, or not more than 7 moles per mole of the photoinitiator. If the content of the redox pair is 1 mole or less per mole of the photoinitiator, the bubble loss reduction effect cannot be ensured, and if it exceeds 13 moles, the bubble loss reduction effect does not increase any more, and the absorption capacity of the produced superabsorbent resin decreases.

[0040] Meanwhile, the reducing agent and the oxidizing agent may each be contained in a content of more than 0.0015 mol%, 0.002 mol% or more, or 0.003 mol% or more, and less than 0.02 mol%, 0.015 mol% or less, or 0.01 mol% or less, relative to 100 mol% of the acrylic acid monomer.

[0041] At this time, the molar ratio of the reducing agent and the oxidizing agent may be 1:1 to 1:2, or 1:1 to 1:1.5.

[0042] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0043] The monomer composition may be prepared by mixing the raw materials, i.e., an acrylic acid-based monomer in which at least a portion of the acidic groups are neutralized, an internal crosslinking agent, a photoinitiator, a thermal initiator, a foaming agent, and a reducing agent and an oxidizing agent which form a redox pair with each other, in a solvent.

[0044] The solvent used in producing the monomer composition may be any solvent capable of dissolving the above-mentioned components, and may be any combination of at least one selected from the group consisting of water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide.

[0045] Meanwhile, in one embodiment of the present invention, the monomer composition may be prepared by: i) adding an alkaline material to a mixture containing an acrylic acid-based monomer, an internal crosslinking agent, and a photoinitiator to neutralize at least a portion of the acid groups of the acrylic acid-based monomer; and ii) adding a thermal initiator, a foaming agent, and a reducing agent and an oxidizing agent that form a redox pair to the mixture obtained after step i). When preparing the monomer composition by the above method, the stability of the process may be ensured by providing time for the monomer solution to be sufficiently mixed and adding the redox pair as late as possible.

[0046] The polymerization of the monomer composition is carried out by radical polymerization by irradiation with light, and can be carried out, for example, in a reactor equipped with a movable conveyor belt. When polymerization is carried out in such a reactor, a sheet-like hydrogel polymer having the width of the conveyor belt is obtained. The thickness of the hydrogel polymer sheet varies depending on the concentration and injection speed of the monomer composition to be injected, but it is usually preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. If the monomer composition is supplied so that the thickness of the sheet-like polymer is excessively thin, production efficiency is low, which is not preferable, and if the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction does not occur uniformly over the entire thickness due to the excessive thickness.

[0047] The polymerization reaction temperature of the monomer composition is not particularly limited, but may be, for example, 80 to 120°C, and preferably 90 to 110°C.

[0048] The water content of the hydrogel polymer may be about 40 to about 80% by weight. Meanwhile, throughout this specification, the "water content" refers to the water content relative to the total weight of the hydrogel polymer, and means the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer using infrared heating. Here, the drying conditions are a method of increasing the temperature to about 180°C from room temperature and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step, and the water content is measured.

[0049] The next step is to dry the resulting hydrogel polymer.

[0050] At this time, if necessary, a coarse pulverization step may be performed before drying in order to increase the efficiency of the drying step.

[0051] In this case, the pulverizer used is not limited in terms of its configuration, and specifically may include any one selected from the group of pulverizing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.

[0052] At this time, the pulverization step is carried out so that the hydrogel polymer has a particle size of about 2 to about 10 mm.

[0053] It is technically difficult to crush the particles to a size of less than 2 mm due to the high water content of the hydrous gel polymer, and the crushed particles may aggregate with each other. Furthermore, if the particles are crushed to a size of more than 10 mm, the efficiency increase effect of the subsequent drying step is minimal.

[0054] The hydrogel polymer immediately after polymerization, which has been crushed as described above or has not been crushed, is dried. At this time, the drying temperature in the drying step may be about 150 to about 250°C. If the drying temperature is less than 150°C, the drying time may be too long, and the physical properties of the superabsorbent polymer may be deteriorated. If the drying temperature is more than 250°C, only the polymer surface may be dried excessively, and fine powder may be generated in the subsequent crushing step, and the physical properties of the superabsorbent polymer may be deteriorated. Therefore, the drying is preferably performed at a temperature of about 150 to about 200°C, more preferably at a temperature of about 160 to about 180°C.

[0055] Meanwhile, the drying time is about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0056] The drying method of the drying step can be selected and used without any limitation on the composition as long as it is a method usually used for drying a hydrogel polymer. Specifically, the drying step can be performed by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such a drying step can be about 0.1 to about 10% by weight.

[0057] Next, the dried polymer obtained through the drying step is pulverized.

[0058] The polymer powder obtained after the pulverization step may have a particle size of about 150 to about 850 μm. Specific examples of the pulverizer used to pulverize to such a particle size include a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, and a jog mill, but the present invention is not limited to the above examples.

[0059] In addition, the polymer powder obtained after the pulverization step may be classified according to particle size, and the polymer powder may be classified to a certain weight ratio according to the particle size range.

[0060] Next, the surface of the dried and pulverized polymer, i.e., the base resin, is additionally crosslinked to form a surface crosslinked layer.

[0061] Specifically, after mixing the base resin with the surface cross-linking agent, the mixture is heated to carry out a surface cross-linking reaction on the pulverized polymer.

[0062] The surface cross-linking step is a step of forming a superabsorbent resin having improved physical properties by inducing a cross-linking reaction on the surface of the base resin in the presence of a surface cross-linking agent, and a surface cross-linked layer (surface modified layer) is formed on the surface of the base resin by such surface cross-linking.

[0063] Since the surface cross-linking agent is applied to the surface of the superabsorbent resin particles, the surface cross-linking reaction occurs on the surface of the superabsorbent resin particles, which does not substantially affect the interior of the particles, and improves the cross-linking property on the surface of the particles. Thus, the surface cross-linked superabsorbent resin particles have a higher degree of cross-linking near the surface than in the interior.

[0064] As the surface crosslinking agent, a compound capable of reacting with a functional group possessed by the polymer is used. Examples of the surface crosslinking agent that can be used include polyhydric alcohol compounds, polyhydric epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, and alkylene carbonate compounds.

[0065] Specifically, examples of polyhydric alcohol compounds that can be used include one or more selected from the group consisting of di-, tri-, tetra- or polyethylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.

[0066] In addition, examples of the polyfunctional epoxy compound that can be used include ethylene glycol diglycidyl ether, polyethylene glycol glycidyl ether, and glycidol. Examples of the polyamine compound that can be used include one or more compounds selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and polyamidepolyamine.

[0067] As the haloepoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used. As the mono-, di-, or polyoxazolidinone compound, for example, 2-oxazolidinone can be used.

[0068] The alkylene carbonate compound may be ethylene carbonate, etc. These may be used alone or in combination with each other.

[0069] The content of the surface crosslinking agent to be added can be appropriately selected depending on the type of the surface crosslinking agent to be specifically added and the reaction conditions, but usually, about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight can be used relative to 100 parts by weight of the base resin.

[0070] If the content of the surface cross-linking agent is too low, the surface cross-linking reaction hardly occurs, whereas if the content exceeds 5 parts by weight per 100 parts by weight of the polymer, the surface cross-linking reaction proceeds excessively, which may result in a decrease in absorption properties such as water retention capacity.

[0071] In addition, there is no limitation on the configuration of the method for adding the surface crosslinking agent to the base resin powder. For example, a method of putting the surface crosslinking agent and the base resin powder in a reaction tank and mixing them, a method of spraying the surface crosslinking agent onto the base resin powder, a method of continuously supplying the base resin powder and the surface crosslinking agent to a mixer that is continuously operated and mixing them, etc. can be used.

[0072] When the surface crosslinking agent is added, water may be added in the form of a surface crosslinking solution by mixing with the agent. When water is added, the surface crosslinking agent is advantageously uniformly dispersed in the polymer. In this case, the content of the added water is preferably about 1 to about 10 parts by weight per 100 parts by weight of the base resin in order to induce uniform dispersion of the surface crosslinking agent, prevent the polymer powder from solidifying, and optimize the surface penetration depth of the surface crosslinking agent.

[0073] Meanwhile, a surface modification step is carried out on the base resin by applying heat to the mixture of the base resin and the surface cross-linking solution to raise the temperature.

[0074] The surface modification step is carried out under well-known conditions depending on the type of surface cross-linking agent, for example, at a temperature of 100 to 200° C. for 20 to 60 minutes. In a more specific example, when the surface cross-linking agent is a polyfunctional epoxy compound, the surface modification step is carried out by heating at a temperature of about 120 to about 180° C., or about 120 to about 150° C., for about 10 to about 50 minutes, or about 20 to about 40 minutes. If the temperature of the surface modification step is less than 100° C. or the reaction time is too short, the surface cross-linking reaction does not proceed properly, resulting in low permeability, and if the temperature exceeds 200° C. or the reaction time is too long, a problem of reduced water retention may occur.

[0075] The temperature raising means for the surface modification reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, or hot oil, but the present invention is not limited to this, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat rise. On the other hand, examples of a heat source that can be directly supplied include heating by electricity and heating by gas, but the present invention is not limited to the above examples.

[0076] After the surface modification step, the resulting superabsorbent resin powder may be further classified according to particle size.

[0077] The superabsorbent polymer prepared by the above-mentioned method has a porous structure with a large number of small and uniform pores, and therefore exhibits excellent absorption properties.

[0078] For example, the superabsorbent resin may have a vortex time of 35 seconds or less, or 33 seconds or less, or 30 seconds or less, or 29 seconds or less, or 25 seconds or less. The smaller the vortex time, the better the vortex time. The lower limit of the vortex time is theoretically 0 seconds, but for example, the vortex time may be 5 seconds or more, 10 seconds or more, or 12 seconds or more.

[0079] The superabsorbent polymer may also have a water retention capacity (CRC) measured according to EDANA method WSP 241.3 of 25 g / g or more, or 29 g / g or more, or 32 g / g or more, and 40 g / g or less, or 38 g / g or less, or 35 g / g or less.

[0080] The superabsorbent polymer may also have an absorbent capacity under pressure (AUL) at 0.9 psi, measured according to EDANA method WSP 242.3, in the range of about 20 g / g or more, or 22 g / g or more, and about 35 g / g or less, or about 33 g / g or less, or about 30 g / g or less.

[0081] Hereinafter, preferred examples will be presented to deepen understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention. It is of course understood that such changes and modifications fall within the scope of the appended claims. EXAMPLES

[0082] Example 1 A monomer solution was prepared by mixing 100 parts by weight of acrylic acid with 0.5 parts by weight of polyethylene glycol diacrylate (weight average molecular weight 500 g / mol) as an internal crosslinking agent and 0.009 parts by weight of Irgacure® 819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, Ciba) as a photoinitiator. Next, the monomer solution was continuously supplied by a metering pump while simultaneously continuously line mixing 140 parts by weight of 31% by weight aqueous sodium hydroxide solution to prepare an aqueous monomer solution. At this time, it was confirmed that the temperature of the aqueous monomer solution had risen to 72°C or higher due to the heat of neutralization, and then the temperature was allowed to cool to 40°C. When the temperature was cooled to 40°C, 0.225 parts by weight of solid sodium bicarbonate was added to the monomer aqueous solution as a blowing agent, 5.6 parts by weight of 4% sodium persulfate aqueous solution as a thermal initiator, and sodium metabisulphite (SMBS) and sodium persulfate (SPS) were added as a reducing agent and an oxidizing agent forming a redox pair at 0.018 mol% relative to 100 mol% of acrylic acid. The solution was poured into a Vat-shaped tray (15 cm wide x 15 cm long) in a square polymerization vessel preheated to 80°C with a light irradiation device installed on top, and the polymerization reaction was started by irradiating light. After irradiating light for 60 seconds, the reaction was continued for an additional 120 seconds to obtain a sheet-shaped hydrogel polymer.

[0083] The hydrogel polymer was uniformly sprayed with 150g of water for lubrication, and then pulverized with a chopper having a 10mm hole plate. The pulverized hydrogel polymer was dried in a dryer capable of shifting the airflow up and down. The hydrogel polymer was uniformly dried by flowing 180°C hot air from bottom to top for 15 minutes, and then again from top to bottom for 15 minutes, so that the moisture content of the dried powder was about 2% or less. The dried polymer was then pulverized in a pulverizer and classified to obtain a base resin powder with a particle size of 150 to 850μm.

[0084] 100 parts by weight of the base resin powder was sprayed with 10 g of a surface crosslinking agent aqueous solution containing 0.12 parts by weight of polyethylene glycol diglycidyl ether (Glyether (registered trademark) EJ1030S, JSI Co., Ltd.), and stirred at room temperature to mix so that the surface crosslinking agent aqueous solution was uniformly distributed on the base resin powder. Next, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor and subjected to a surface crosslinking reaction for 40 minutes under a condition of 140°C. The powder obtained after the surface crosslinking reaction was classified using a standard mesh sieve according to the ASTM standard to produce a superabsorbent resin with a particle size of 150 to 850 μm.

[0085] Example 2 A highly water-absorbent resin was produced in the same manner as in Example 1, except that SMBS and SPS were each added to the aqueous monomer solution in an amount of 0.01 mol % relative to 100 mol % of acrylic acid.

[0086] Example 3 A highly water-absorbent resin was produced in the same manner as in Example 1, except that SMBS and SPS were each added to the aqueous monomer solution in an amount of 0.005 mol % relative to 100 mol % of acrylic acid.

[0087] Example 4 A highly water-absorbent resin was produced in the same manner as in Example 1, except that SMBS and SPS were each added to the aqueous monomer solution in an amount of 0.003 mol % relative to 100 mol % of acrylic acid.

[0088] Example 5 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.018 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0089] Example 6 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.01 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0090] Example 7 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.005 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0091] Example 8 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.003 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0092] Comparative Example 1 A superabsorbent resin was prepared in the same manner as in Example 1, except that no redox couple was added to the aqueous monomer solution.

[0093] Comparative Example 2 A superabsorbent resin was produced in the same manner as in Example 1, except that SMBS and SPS were each added to the aqueous monomer solution in an amount of 0.02 mol % relative to 100 mol % of acrylic acid.

[0094] Comparative Example 3 A highly water-absorbent resin was produced in the same manner as in Example 1, except that SMBS and SPS were each added to the aqueous monomer solution in an amount of 0.0015 mol % relative to 100 mol % of acrylic acid.

[0095] Comparative Example 4 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.02 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0096] Comparative Example 5 A superabsorbent resin was produced in the same manner as in Example 1, except that ascorbic acid and hydrogen peroxide were added to the aqueous monomer solution in an amount of 0.0015 mol % relative to 100 mol % of acrylic acid, instead of SMBS and SPS, as a redox couple.

[0097] Experimental Example The physical properties of the superabsorbent resins of the above-mentioned Examples and Comparative Examples were measured by the methods described below, and the results are summarized in Table 1.

[0098] (1)Centrifugal Retention Capacity (CRC) Using EDANA method WSP 241.3 as the standard, the centrifugal water retention capacity of each superabsorbent resin was measured by the following method.

[0099] 0.2g (W0) of superabsorbent resin sample with a particle size of 300-600μm was evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9% by weight sodium chloride aqueous solution) at room temperature. After 30 minutes, the envelope was dehydrated for 3 minutes at 250G using a centrifuge, and the mass of the envelope W2 (g) was measured. The same operation was performed without using the resin, and the mass W1 (g) at that time was measured. The CRC (g / g) was calculated using the obtained masses according to the following formula.

[0100] [Formula 1] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0101] (2) Absorbency under Load (0.9 AUL) The absorbency at 0.9 psi of each resin was measured according to EDANA method WSP 242.3. When measuring the absorbency at pressure, a superabsorbent resin sample having a particle size of 300 to 600 μm was used, as in the CRC measurement.

[0102] A stainless steel 400 mesh wire net was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. Under conditions of room temperature and humidity of 50%, water-absorbent resin W3(g) (0.16g) was evenly spread on the wire net, and a piston capable of applying a load of 0.9 psi evenly on the wire net was made to be slightly smaller than the outer diameter of 25 mm, with no gap between it and the inner wall of the cylinder, and to not hinder the up and down movement. At this time, the weight W4(g) of the device was measured.

[0103] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and physiological saline (0.9 wt% sodium chloride aqueous solution) was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under load for one hour. After one hour, the measuring device was lifted and its weight W5 (g) was measured.

[0104] The obtained masses were used to calculate the absorbency under pressure (g / g) according to the following formula.

[0105] [Formula 2] 0.9AUL(g / g)=[W5(g)‐W4(g)] / W3(g)

[0106] (3) Water absorption rate (vortex time, seconds) The water absorption rate (vortex time) was measured according to the Japanese standard method (JIS K 7224).

[0107] Specifically, 50 mL of physiological saline (0.9 wt% sodium chloride aqueous solution) at 24°C and a magnetic bar (diameter 8 mm, length 31.8 mm) were placed in a 100 mL beaker and stirred at 600 rpm. 2.0 g of a superabsorbent resin with a particle size of 300 to 600 μm was added to the stirred physiological saline, and the time until the vortex disappeared was measured in seconds to calculate the water absorption rate.

[0108] [Table 1]

[0109] Referring to Table 1, it can be seen that the superabsorbent resins of Examples 1 to 8, to which a reducing agent and an oxidizing agent that form a redox pair were added, exhibited significantly improved water absorption speeds and had equivalent or greater centrifugal water retention capacity and pressurized absorption capacity compared to the superabsorbent resin of Comparative Example 1, to which no redox pair was added. However, it can be seen from Comparative Examples 2 to 5 that when the amount of redox pair added was 1 mol or less or more than 13 mol per mol of photoinitiator, no improvement in water absorption speed was obtained.

Claims

1. preparing a monomer composition by mixing an acrylic acid monomer having an acidic group, at least a portion of which is neutralized; an internal crosslinking agent; a photoinitiator; a thermal initiator; a foaming agent; and a reducing agent and an oxidizing agent which form a redox pair with each other; preparing a hydrogel polymer by cross-linking the monomer composition; drying and grinding the hydrogel polymer to form a base resin in powder form; and A method for producing a superabsorbent resin, comprising the step of additionally crosslinking a surface of the base resin in the presence of a surface crosslinking agent to form a surface crosslinked layer, The reducing agent and the oxidizing agent are each present in an amount of from more than 1 mole to 13 moles or less per mole of the photoinitiator; The foaming agent is contained in an amount of 0.05 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer.

2. The method for producing a highly water-absorbent resin according to claim 1, wherein the reducing agent and the oxidizing agent are each contained in an amount of 2 to 12 moles per mole of the photoinitiator.

3. The method for producing a highly water-absorbent resin according to claim 1, wherein the reducing agent and the oxidizing agent are each contained in an amount of more than 0.0015 mol % and less than 0.02 mol % relative to 100 mol % of the acrylic acid monomer.

4. 2. The method for producing a superabsorbent polymer according to claim 1, wherein the reducing agent is sodium metabisulfite and the oxidizing agent is sodium persulfate.

5. The method for producing a highly absorbent resin according to claim 1, wherein the reducing agent is ascorbic acid and the oxidizing agent is hydrogen peroxide.

6. 2. The method for producing a superabsorbent resin according to claim 1, wherein the foaming agent is at least one selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate.

7. The step of preparing the monomer composition comprises: i) adding an alkaline substance to a mixture including an acrylic acid-based monomer, an internal crosslinking agent, and a photoinitiator to neutralize at least a portion of the acid groups of the acrylic acid-based monomer; and ii) adding a thermal initiator, a blowing agent, and a reducing agent and an oxidizing agent which are in a redox pair to the mixture obtained after step i),

Citation Information

Patent Citations

  • Color-stable superabsorbent polymer composition

    JP2006522181A

  • Method for agglomerating superabsorbent particles

    JP2006528708A

  • Method for producing a water-absorbent polymer with high absorption rate

    JP2014516378A

  • Superabsorbent polymer having high absorbency and method for producing the same

    JP2014533312A

  • Highly water-absorbent resin and method for producing the same

    JP2021509688A